'Blurred lines': Anti-doping, national policies, and the performance and image enhancing drug (PIED) market in Belgium and The Netherlands. Issue 3 (June 2016) - van de Ven, Katinka
Abstract: Background: Due to a growing awareness of the consumption of performance and image enhancing drugs (PIEDs), and the perceived associated adverse health effects, PIEDs have increasingly come to be viewed as a serious public health problem. However, there seems to be a tendency amongst policymakers to frame recreational PIED use as an issue within sport, and to call for the same types of policies that are being used in anti-doping. This paper explores the ways in which national PIED policies in The Netherlands and Belgium and anti-doping measures are intertwined, and how the different approaches adopted in each nation are impacting on the illicit PIED market. Methods: This article draws on two years of fieldwork in various bodybuilding settings, 47 semi-structured interviews with individuals who are directly or indirectly involved in the PIED market, and a content analysis of 64 PIED-dealing cases initiated by criminal justice agencies in The Netherlands and Belgium. Findings: The data indicates that both countries do not appear to be successful in disrupting the illicit PIED market. In Belgium the demand for PIEDs seems to be unaffected by the threat of criminal penalties or disciplinary measures and continued enforcement may worsen present health risks. However, due to the limited priority of controlling PIED production and/or distribution in The Netherlands, a large underground culture has developed, stimulated by the Internet, in which individuals and groups manufacture and distribute their own PIEDs. In both countries, the intertwinement of national efforts to address recreational PIED use, with sport policy, hinders the exploration of alternative measures and/or the inclusion of other substances and using populations in prevention and harm reduction initiatives. Conclusion: Both the regulation and law enforcement practices around PIEDs in Belgium and the limited priority in The Netherlands may be contributing to increasing and exacerbating existing harms.